THE STUDENTS’ ENGLISH PRAGMATIC COMPETENCE IN UNDERSTANDING CROSSCULTURAL COMMUNICATION: A STUDY AT XI GRADE STUDENT OF SMK NEGERI 1 BATULAYAR - Derah Mayanto (Lingual: Journal of Language and Culture, 2016)
This paper investigates the students’ English pragmatic competence in understanding crossculturalcommunication. There were eighteen communicative situations designed in threedifferent speech acts namely; handling complaint, request and refusal. The situationspresented were very similar to the authentic situation that students found during the joborientation for six months in tourism industry. Three instruments were used in collecting thedata; questionnaires, discourse completion tests (DCTs) and interview. The multiple choicequestionnaire was used to investigate the students’ pragmatic understanding in three deferentspeech acts. Meanwhile DCTs was used to investigate the students’ pragmatic knowledge ingiving response to the given situations related to three different speech acts. Interviewquestion was used to clarify the missing information and to strengthen the reason why suchresponses were given in questionnaire and in DCTs. The sample of this study was 92 XIGrade students from Hotel Accommodation Program (AP) at SMK Negeri 1 Batulayar. Theresult show that the students ability in understanding pragmatic is considered very low, theyonly can understand the utterance from the literal meaning of words and phrases, but theimplied meaning of some particular utterances were uneasy to deal with. It is seen from thereported data that the average of the students’ responses in understanding pragmatics of thethree different speech acts is only 12.7%. The second three different speech acts in discoursecompletion test (DCTs) was also about giving response to the complaint, request and refusal.DCTs were used to investigate the students’ ability in using their pragmatic knowledge toresponse the nine situational communicative designed. The finding show that the students’ability in giving the written response were vary and less impressive. The written responsesin three different speech acts prompt were potentially led to a pragmatic inability inmaintaining the smooth conversation in various situations.